The effect of 1,25-dihydroxycholecalciferol on renal tubular reabsorption of phosphate, intestinal absorption of calcium and bone histology in hypophosphataemic renal tubular rickets. - Russell, R; Smith, R; Preston, C; Walton, R; Woods, C; Henderson, R; Norman, A (1975)
1. 1,25-Dihydroxycholecalciferol (1,25-(OH)2-D3) was given at a dose of 5-0 nmol (2-1 mug) daily by mouth for 4-12 days to three patients with hypophosphataemic (type I), vitamin D-resistant rickets. 2. 1,25-(OH)2-D3 increased intestinal absorption and urinary excretion of calcium without significant effect on the renal handling of phosphate or its plasma concentration. 3. It is concluded that in this type of vitamin D-resistant rickets the renal phosphate abnormality is unlikely to be due to diminished endogenous production of 1,25-(OH)2-D3. 4. The difference between this condition and other hypophosphataemic states is discussed.